Analysis of the Relationship between the Quality of Presence of Destination through Online Travel Contexts, Attitude, and Intention; Case of Iran - Ghaderi, Zahed; Shahabi, Rasoul; Qezelbash, Amir Hossein (Journal of Tourism Management Research, 2020)
Advancing in the Internet and digital breakthroughs in communication tools bring various transformations in tourism industry requiring invasive studies about travel destinations online presence, and tourists’ online behavior. It is important to investigate and analyze the role of online environment, in general, and tourism online contexts, in particular on the formation of tourist’s desires and attitude toward the destination in order to manage and provide an appropriate image of the destination. The current study examined how online travel materials affect tourist attitudes and decision- making in visiting a destination. A quantitative research method, using a sample of 456 respondents of international tourists visiting Iran in 2016 was applied. Applying partial least square method, the results showed that the quality of websites, satisfaction, trust, and perceived usefulness have a positive impact on the tourists’ attitude and destination selection. Furthermore, perceived usefulness of the destination online contexts (DOCs) positively affects the user’s satisfaction and it also positively affects the continuous intention to use DOCs. Unlike previous researches we also found a positive relationship between design quality and DOCs confirmation. In addition, theoretical and practical implications of the findings were discussed.